Web Interface Security Vulnerabilities of European Academic Repositories - Formanek, Matus; Zaborsky, Martin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
The given analysis summarizes the status quo of the level of security of web interfaces of selected European academic repositories in the field of library and information science. It focuses on the presence and qualities of the secure HTTPS protocol via SSL/TLS protocols. The security of the transmitted data is particularly important in the network environment of the Internet, especially if log-in user data is transmitted. Disclosure may have a direct impact on saved digital objects and their metadata which together represent the most valuable parts of systems of digital libraries and repositories. Furthermore, the paper points to the most noticeable vulnerabilities of protocols of web interfaces and presents practical recommendations for the expert public. These may contribute to the increase of the level of security of the discussed systems. The authors base their proposals on the currently available scientific publications and scientific articles about the given topic.